SERTIFIKASI HALAL SEBAGAI INOVASI KULINER : ANALISIS DAMPAKNYA TERHADAP DAYA TARIK PASAR - Rochmawati, Tiara (Jurnal Daya Saing, 2025)
Halal certification plays an important role in increasing market appeal in the culinary industry, especially in Indonesia, which has the largest Muslim population. This study aims to analyze the impact of halal certification on culinary innovation in Rokan Hulu Regency. The type of research used is qualitative with a case study approach, which allows researchers to gain an in-depth understanding of the phenomenon being studied. Research informants consist of culinary SME owners and consumers with experience related to halal certification. Data collection techniques were conducted through in-depth interviews. The data obtained were then analyzed using triangulation techniques to ensure the validity and reliability of the information. The research findings indicate that halal certification significantly increases consumer confidence, leading to increased demand for culinary products. Additionally, halal certification encourages businesses to innovate in product development, thereby creating a competitive advantage in the market. The managerial implications of this study emphasize the importance for culinary businesses to obtain halal certification as a strategy to enhance market appeal and meet the growing consumer demand for halal-certified products.